Clinical performance of posterior resin composite restorations after up to 33 years. Issue 4 (April 2022) - Da Rosa Rodolpho, Paullo A.; Rodolfo, Bruna; Collares, Kauê; Correa, Marcos B.; Demarco, Flavio F.; Opdam, Niek J.M.; Cenci, Maximiliano S.; Moraes, Rafael R.
Abstract: Objectives: This retrospective study evaluated the performance of posterior composites after up to 33 years of clinical service and investigated factors associated with the risk of failures over time including patient- and tooth-related variables. Methods: Patients who received at least one Class I or Class II direct composite restoration in a private office in 1986–1992 and had follow-up appointments were included. Failures and interventions over time were investigated using the dental records. A follow-up clinical recall was carried out in 2020. Two scenarios were considered: restorations that did not require any intervention (success) or restorations that were repaired and still functional (survival). Multivariate Cox regression analyses and Kaplan-Meier curves were performed using success and survival rates (p < 0.05). Results: One hundred patient records and 683 restorations were included. A total of 353 failures were reported (success rate= 48%). Main reasons for failure were fracture and secondary caries. Most interventions after failures were repairs. Replacements were registered in 183 cases (survival rate= 73%). Annual failure rates were below 2.5% (success) and 1.1% (survival). Larger restorations and maxillary molars had higher failure risks. No significant differences in success rates among different resin composites was observed. A typical observation in this sample of restorations was the presence of moderate to advanced signs of aging, including marginal and surface staining, wear, chipping, changes in anatomical shape and translucency. Clearly aged restorations were still clinically satisfactory. Significance: This long-term, practice-based study indicates that resin composites can be used to restore posterior teeth with a long-lasting durability.